The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.17221/179/2011-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the contents of impurities and seed hulls on the quality of cold-pressed sunflower oil

Abstract: Dimić E., Premović T., Takači A. (2012): Effects of the contents of impurities and seed hulls on the quality of cold-pressed sunflower oil. Czech J. Food Sci., 30: 343-350.The effects of different contents of impurities and seed hulls in the raw material on the sensory characteristics, chemical quality, and oxidative stability of sunflower oil prepared by the procedure of cold pressing on a screw press were investigated. It was found that the presence of impurities (up to 10%) and hulls (up to 32%) had an adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Sensory panel members were needed so as to score the samples from 1 to 5. (1 = Very bad; 2 = bad; 3 = good; 4 = very good; 5 = excellent) (Dimić et al., 2012; Janiaski et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Sensory panel members were needed so as to score the samples from 1 to 5. (1 = Very bad; 2 = bad; 3 = good; 4 = very good; 5 = excellent) (Dimić et al., 2012; Janiaski et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The more the soluble substances in oil, the greater the bend or refraction of light through it. The percentage impurity is a measure of the amount of foreign substances such as hulls from the groundnut and sand particles in fats and oils (Dimic et al, 2012). The percentage impurity values ranged between 0.25 and 0.44%.…”
Section: Physical Properties Of Groundnut Oil Extracted With Potashmentioning
confidence: 99%
“…This indicates that potash addition during extraction reduced the quality of oil produced. Dimic et al, (2012) showed that impurities have a negative effect on sensory characteristics such as the taste and odour as well as the chemical quality of oil samples. The presence of impurities also affects colour of the oil samples, giving them a turbid appearance (Dimic et al, 2012).…”
Section: Physical Properties Of Groundnut Oil Extracted With Potashmentioning
confidence: 99%
“…13-15). The appearance of fusty, musty or rancid off -fl avours may result from storage under inappropriate humidity Matthäus, 2008), while the presence of impurities in raw material (up to 10%) exert an adverse eff ect on the sensory characteristics of the oil (Dimić et al, 2012). A positive correlation was found between the level of impurities in seeds and the appearance of woody (r = 0.847), astringent (r = 0.464) and fusty/musty (r = 0.591) off -fl avours, as well as strawy (r = 0.630) sensory attribute.…”
Section: Sensory Assessment Of Oilsmentioning
confidence: 99%